PELAKSANAAN PENDIDIKAN KARAKTER (Suatu Tinjauan Kritis Terhadap Praktek Pendidikan Karakter Di SMAK St. Paulus Saumlaki Kabupaten Maluku Tenggara Barat) - Reresi, Marsianus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2017)
Character Education as a process of formation of character values of the students. The fundamental question of this qualitative pilot study concerns the practice of the character education at the SMAK high school St.Paulus in Saumlaki. This research makes use of a descriptive analytical method and is based on the awareness towards the importance of character education, and finds that the SMAK St.Paulus Saumlaki performs a character education in its program of personal development, which is integrated in activities of study, culture and social attitude. Prominent values that are detected involve religion, discipline, sense of responsibility, friendship, intercommunication and care for environment and society.